Effect of motivational interviewing on oral and dental health of adolescents with fixed orthodontic appliances - Shima Ziari; Mahdia Gholami; Sarvin Sarmadi (Journal of Craniomaxillofacial Research, 2022)
Introduction: Orthodontic appliances increase the risk of dental caries and gum disease. Since it is rather difficult to maintain oral hygiene in patients with fixed orthodontic appliances due to the presence of brackets, bands, and arch wires, they should be persuaded to take care of their oral cavity. Therefore, the present study was conducted to evaluate the effect of an oral and dental health educational intervention using motivational interviewing in adolescents with fixed orthodontic appliances. Materials and Methods: Thirty adolescents with fixed orthodontic appliances aged 12-16 years presenting to orthodontics departments of school of dentistry, Tehran University of Medical Sciences, received individual counselling, verbal guidelines, and training for correct brushing and flossing techniques by a senior student of dentistry during a 20-minute motivational interview. To evaluate the effect of the intervention, oral health behaviors including brushing, flossing, and consumption of sugary snacks were collected in a self-report manner. Moreover, plaque and gingival indexes were measured before and one-month post intervention. The SPSS software version 23 was used for data analysis. Results: Among oral health behaviors, optimal frequency of brushing increased after the intervention (p=0.002). The mean plaque index was 0.99±0.43 before and 0.37±0.16 after the intervention, indicating a significant difference (p<0.001). Moreover, the mean gingival index (average inflammation) was 0.99±0.56 before the intervention, which improved to 0.30±0.20 after the intervention (p<0.001). Conclusion: Educational intervention based on motivational interviewing reduced dental plaques and gingival inflammation and increased the frequency of brushing in the short term among adolescents with fixed orthodontic appliances. Keywords: Adolescent; Behavioral sciences; Fixed orthodontic appliances; Motivational interviewing; Oral health.